Adjuvant cyclin‐dependent kinase 4/6 inhibition in hormone receptor–positive breast cancer: One Monarch to rule them all?. Issue 18 (28th May 2021) - Dhakal, Ajay; Falkson, Carla; O'Regan, Ruth M.
Abstract : The use of cyclin‐dependent kinase 4/6 (CDK4/6) inhibitors has dramatically improved outcomes for patients with metastatic, hormone receptor (HR)–positive breast cancer. Because of the continued high rate of relapse in patients with node‐positive, HR‐positive disease, evaluating these agents in the adjuvant setting is the logical next step. Three adjuvant CDK inhibitor trials have been reported to date, with only 1 of them showing a statistical advantage for the CDK inhibitor in comparison with endocrine therapy alone. These trials have key similarities and differences that could explain the disparate results. The one positive trial has a relatively short follow‐up, and continued analysis is critical to confirm the benefit of adjuvant CDK inhibition in this setting. It is imperative that predictive biomarkers be determined so that these agents can be used in the patients most likely to benefit and thus the additional toxicity and expense can be avoided in those who do not require these agents. Lay Summary: There is a critical need for new agents to prevent relapse in patients with hormone receptor–positive breast cancer. Trials to date evaluating cyclin‐dependent kinase inhibitors, which decrease how quickly cancer cells multiply, have shown mixed results, with only 1 trial demonstrating that these agents decrease recurrence. Abstract : Only 1 of 3 trials that have evaluated the use of adjuvant cyclin‐dependent kinase (CDK) inhibitors to date has shown positive results in comparison with endocrine therapy alone in patients with high‐risk, hormone receptor–positive breast cancer. It is essential that we determine through the identification of robust biomarkers which patients are likely to benefit from adjuvant CDK inhibitors on account of the toxicity and added cost of these agents.